Influence d’une faculte´ des sciences de l’administration sur les valeurs humaines de ses e´tudiants - Petrof, John V.; Sayegh, Elie E.; Vlahopoulos, Pandelis (Canadian Journal of Higher Education, 1981)
This study indicates that schools of business influence the personal values of their students. Current management education produces individuals who have ego-centered rather than society or other-centered values. Given this framework the authors raise the question, "Do business schools produce the type of manager that is needed in the future?".